(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Assam has made energetic efforts since 2015 towards achieving the Sustainable Development Goals (SDGs). Cognizant of the state’s weak improvement in development, its recent governments irrespective of political affiliation adopted the SDGs and Assam became the first state in India to do so. The paper discusses in detail the steps taken so far which include overall vision of SDG-fulfilled Assam in 2030; and contribution and challenges in higher education and sustainable development in Assam. The Assam experience has many important lessons. These include the criticality of inspiring staff at all levels to instill the SDGs in every aspect of their work and the role of leadership in this respect; proactively forging partnerships with all stakeholders including the administration and the judiciary and creating an environment for such partnerships to flourish; the general need for adopting a result and outcome-based development process that the SDGs represent abandoning narrow departmental and output-based activity and perform. These would require initiating institutional and organizational changes counting to ensure that major improvements take place in project implementation processes. Also essential is inculcating a culture of modernism –including technological innovation–in every sphere of public service; and developing effective coordinating mechanisms to ensure that all concerned stakeholders work synergistically to achieve the SDG outcomes. Also, very critical is the role of national and global partners in supporting Assam’s earnest efforts as the resource, information and capacity gaps that Assam faces are too large for it to fill through its own means –even with its best efforts.